Exaggerated plasma Interleukin 6, Interleukin 10, and Subsequent Development of Health Care–Associated Infections in Patients With Sepsis. Issue 2 (March 2015) - Umberger, Reba; Thompson, Carol L.; Cashion, Ann K.; Kuhl, David; Wan, Jim; Yates, Charles R.; Muthiah, Muthiah P.; Meduri, Gianfranco Umberto
<x xml:space="preserve">Abstract</x> Background: Health care–associated infections (HAIs) are the target of many well-known preventive measures in the intensive care unit (ICU); however, little is known about post–sepsis-induced immunosuppression. Objectives: This study explores the relationship between baseline plasma levels of inflammatory cytokines interleukin 6 (IL-6), IL-10, and IL-6:IL-10 and subsequent development of HAIs in patients with admitted with sepsis. Methods: Prospective observational study was conducted among veterans admitted to the ICU with sepsis and monitored daily through ICU discharge (up to 28 days) to investigate HAI development. Baseline plasma IL-6 and IL-10 levels were measured with a multiplex bead based assay. Exaggerated systemic inflammation was defined as the fourth quartile (IL-6 and IL-10) compared with other quartiles. Results: We recruited 78 patients over 18 months, primarily older (65.5 ± 12.6 years) men (94.9%) with underlying comorbidities (93.9%) and a high severity of illness (Acute Physiologic and Chronic Health Evaluation II score 20.6 ± 6.4). Seventeen patients (21.7%) developed at least 1 HAI, and candidemia was the leading infection. Patients with exaggerated baseline systemic inflammation developed a nonsignificantly higher proportion of HAI as compared with those not developing HAI (IL-6: 31.6% vs 18.6%, P = .55; IL-10: 26.3% vs 20.3%, P = .43). Discussion: Patients with exaggerated systemic inflammation had a higher severity of illness, but not a statistically significant higher incidence of HAI. A larger, more adequately powered sample with serial cytokine measures is needed. Routine surveillance cultures are needed. Health care–associated infection may occur in the absence of fever, and the emerging incidence of Candida is a concern. Immune suppression after sepsis should be recognized as a risk for HAI development. Antibiotic therapy should be targeted with prompt de-escalation of empiric therapy per established guidelines to preserve normal flora.